Induced Opening of the Gastroesophageal Junction Occurs at a Lower Gastric Pressure in Gerd Patients and in Hiatal Hernia Subjects than in Normal Control Subjects. (2nd March 2010) - Vegesna, Anil; Besetty, Ramashesai; Kalra, Amit; Farooq, Umar; Korimilli, Annapurna; Chuang, Keng yu; Fisher, Robert; Parkman, Henry; Miller, Larry
Abstract : Purpose . To determine intragastric pressure threshold for inducing gastroesophageal junction (GEJ) opening in normal control subjects with and without hiatal hernia, and in patients with gastroesophageal reflux disease. Methods . This study was performed in 13 normal volunteers, 5 volunteers with hiatal hernia, and 3 patients with gastroesophageal reflux disease. During endoscopy a pressure transducer was used to measure baseline gastric pressures. The pressure in the stomach was measured while air was insufflated into the stomach until the gastroesophageal junction opened on endoscopic view. Results . There were two patterns of GEJ opening in normal volunteers. The mean opening pressure for Gastroesophageal junction in normal pattern-I, normal pattern-II, hiatal hernia, and Gastroesophageal reflux patients was 11.5, 12.6, 3.4, and 1.3 mmHg, respectively. Conclusions . GEJ opening is induced at a significantly lower pressure in subjects with hiatal hernia and in patients with gastroesophageal reflux disease than in normal volunteers.